Pengaruh Model Pembelajaran Course Review Horay Berbantuan Media Permainan Bingo terhadap Hasil Belajar Siswa - Rida Munggarani; Raden Roro Suci Nurdianti; Kurniawan Kurniawan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Low student learning outcomes in economics in class XI IPS SMAN 1 Manonjaya are the focus of the study. The study aims to see the effect of the course review horay model assisted by bingo game media on student learning outcomes in economics, the method used is a quasi-experiment accompanied by a quantitative approach accompanied by data acquisition techniques through multiple choice questions. Class XI IPS SMAN 1 Manonjaya as many as 164 students became the population in the study. Class XI IPS 1 and XI IPS 2 were used as research samples using the purposive sampling technique. The results of the study showed that there was a gap in increasing student learning outcomes in the experimental class that applied the course review horay learning model assisted by bingo game media with the control class that applied the conventional model. This can be seen in the N-Gain value. For the experimental class, the N-gain value was 0.71 even though the control class was 0.43. This resulted in the average N-gain value of the experimental class being higher than the control class. Therefore, based on the independent samples t test, it produces a significance (2-Tailed) of 0.000 <0.05 or 5%. Therefore, the findings state that the course review horay model assisted by bingo game media influences the improvement of student learning outcomes.